PENGEMBANGAN POLA BERPIKIR KRITIS SISWA MELALUI PEMBELAJARAN BAHASA INDONESIA YANG KONSTRUKTIVISTIK DI SMP KOTA TONDANO - Agus G Senduk (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aimed to describe a model of the development of the constructivist Indonesian language teaching to optimize students’ critical thinking patterns. The study was carried out by the teachers of Junior High Schools in Tondano. The indicators of such teaching were not so apparent (only 28.42%) in the teaching andlearning process in the classroom. In other words, the constructivist teaching behavior was very poor in relation to the development of the students’ critical thinking patterns. The following indicators showed that the constructivist teaching was not implemented yet: (1) the students were not actively involved designing, doing, and assessing the teaching activities in the classroom; (2) they were not motivated to learn from their friends in the classroom through cooperation, team work, or selfreflection;the cooperative activities were not considered as the main stimulus in the learning process; (3) the teaching and learning activities were not related to the real world, world issues or concrete problems around the students’ life; (4) the students’various life contexts were not employed and developed and their prior knowledge was not taken into account in the learning process; and (5) the teachers did not act as facilitators in the students’ learning activities.